Back Cover: Bifunctional Silver(I) Complex‐Catalyzed CO2 Conversion at Ambient Conditions: Synthesis of α‐Methylene Cyclic Carbonates and Derivatives (ChemSusChem 5/2015). Issue 5 (20th February 2015) - Song, Qing‐Wen; Chen, Wei‐Qiang; Ma, Ran; Yu, Ao; Li, Qiu‐Yue; Chang, Yao; He, Liang‐Nian
<x xml:space="preserve">Abstract</x> The Back Cover image shows utilization of CO2, which holds great promise as a sustainable feedstock rather than a waste. The idea of the whole image comes from an ancient Chinese Taiji (Taoism) nose map: on the one hand, CO2 is an exhaust gas and a greenhouse gas; on the other hand, it can be upgraded into numerous fruits through an ingenious methodology, namely catalysis, which can be considered as a great contribution towards realizing a beautiful world and better life. Incorporation of CO2 into chemicals can be achieved through a catalytic pathway at ambient conditions. This metal‐promoted protocol can be applied to various transformations of CO2 into value‐added products on a 10 g scale. The synergic activation mode based on the bifunctional silver(I) catalyst used is supported by DFT studies, NMR spectroscopy, 13C labelling, and control experiments. More details can be found in the Full Paper by Song et al. on page 821 (DOI: 10.1002/cssc.201402921).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>